Cerebellar synaptic protein expression in schizophrenia. - Eastwood, S; Cotter, D; Harrison, P (2001)
A cortico-subcortico-cerebellar neural circuit has been postulated to be important in the pathophysiology of schizophrenia. This study investigated whether there are synaptic changes in the cerebellum to accompany its putative involvement in the disorder. We measured the expression of three synaptic proteins (synaptophysin, complexin I and complexin II) in the cerebellar cortex of 16 subjects with schizophrenia and 16 controls using in situ hybridisation histochemistry and immunoautoradiography. Complexin I and II are expressed predominantly by inhibitory and excitatory neurones respectively. In schizophrenia, synaptophysin mRNA was decreased, as was complexin II and its mRNA. Complexin I mRNA and protein levels were unaltered. Expression of the mRNAs in the rat cerebellum was unaffected by 2 weeks administration of antipsychotic drugs (haloperidol, chlorpromazine, risperidone, olanzapine or clozapine). We conclude that there is synaptic pathology in the cerebellum in schizophrenia. By disrupting neural circuits, the alterations may contribute to the cerebellar dysfunction thought to occur in the disorder.